2020
DOI: 10.1016/j.ijpe.2020.107886
|View full text |Cite
|
Sign up to set email alerts
|

Exploring supply chain structural dynamics: New disruptive technologies and disruption risks

Abstract: We discuss recent developments in exploring supply chain structural dynamics. We focus on both positive (i.e., new disruptive technologies) and negative (i.e., disruption risks) triggers of the structural dynamics in complex supply chain networks. We discuss papers in the special issue which focus on supply chain structural dynamics using different methods, collating and presenting recent research in the field. In particular, the ripple effect, blockchain, network resilience, data analytics, and service platfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(46 citation statements)
references
References 61 publications
2
44
0
Order By: Relevance
“…Shih ( 2020 ) supported this condition of current pandemic, where the unavailability of human labour is the most critical issue which potentially harms the operations of the supply chain. Subsequently, many researchers suggested that technologies of industry 4.0 such as AI, the IoT, and big data analytics, can help in building resilience in SCM (Dolgui and Ivanov 2020 ; Birkel and Hartmann 2020 ; Nayal et al 2021 ).…”
Section: Discussion and Proposed Research Modelmentioning
confidence: 99%
“…Shih ( 2020 ) supported this condition of current pandemic, where the unavailability of human labour is the most critical issue which potentially harms the operations of the supply chain. Subsequently, many researchers suggested that technologies of industry 4.0 such as AI, the IoT, and big data analytics, can help in building resilience in SCM (Dolgui and Ivanov 2020 ; Birkel and Hartmann 2020 ; Nayal et al 2021 ).…”
Section: Discussion and Proposed Research Modelmentioning
confidence: 99%
“…(Dolgui et al, 2018 ; Ivanov & Dolgui, 2020 ; Ivanov et al, 2017 ) highlighted the crucial role of reconfiguration to mitigate the ripple effect and to deal with supply chain disruptions. Besides, (Dolgui & Ivanov, 2020 ; Dolgui et al, 2020 ) showed that RSC has an important role in ensuring competitiveness in the markets.…”
Section: Introductionmentioning
confidence: 99%
“…The ripple effect occurs when a disruption, rather than remaining localised or being contained to one part of the SC, cascades downstream and impacts the performance of the entire SC (Dolgui, Ivanov, and Sokolov 2018). Ripple effect is followed by SC structural dynamics (Dolgui and Ivanov 2020;Ivanov 2018) market share and reputation, etc., with adverse effects on the profitability of SC Gupta, Ivanov, and Choi 2020;. Some examples of the ripple effect are as follows:…”
mentioning
confidence: 99%